Circadian rise in maternal glucocorticoid prevents pulmonary dysplasia in fetal mice with adrenal insufficiency - Venihaki, Maria (The National Academy of Sciences, 2000)
The hypothalamic-pituitary-adrenal (HPA) axis, including hypothalamic corticotropin-releasing hormone (CRH) and pituitary corticotropin, is one of the first endocrine systems to develop during fetal life, probably because glucocorticoid secretion is necessary for the maturation of many essential fetal organs. Consistent with this, pregnant mice with an inactivating mutation in the Crh gene deliver CRH-deficient offspring that die at birth with dysplastic lungs, which can be prevented by prenatal maternal glucocorticoid treatment. But children lacking the ability to synthesize cortisol (because of various genetic defects in adrenal gland development or steroidogenesis) are not born with respiratory insufficiency or abnormal lung development, suggesting that the transfer of maternal glucocorticoid across the placenta might promote fetal organ maturation in the absence of fetal glucocorticoid production. We used pregnant mice with a normal HPA axis carrying fetuses with CRH deficiency to characterize the relative contributions of the fetal and maternal adrenal to the activity of the fetal HPA axis, and related these findings to fetal lung development. We found that in the presence of fetal adrenal insufficiency, normal fetal lung development is maintained by the transfer of maternal glucocorticoid to the fetus, specifically during the circadian peak in maternal glucocorticoid secretion.